Diabetic foot care knowledge among type 2 diabetes mellitus patients: a cross-sectional study - Estriana Murni Setiawati; Hamudi Prasestiyo; Putri Nabila Raihana; Patrianto Patrianto (International Journal of Health Science and Technology, 2026)
Diabetic foot ulcers can profoundly affect a patient's life, resulting in a diminished quality of life and a heightened risk of mortality. To avert complications arising from diabetic foot ulcers, it is crucial to possess comprehensive knowledge. This study aims to quantify and evaluate the level of diabetic foot care knowledge among patients with diabetes mellitus. A descriptive cross-sectional research design was utilized. Sample selection was conducted using convenience sampling among patients with diabetes mellitus who met the predetermined inclusion criteria. It focused on 100 patients with type 2 diabetes mellitus who had attended the Internal Medicine Clinic. Participants were selected using the Slovin formula. The study instruments included demographic data and the Foot Care Knowledge Questionnaire. The findings indicated that the majority of respondents were aged 59. Most were female (64 %) and had a high school education (60%). Most of them have self-employed jobs (27%). Marital status shows that the majority are married, 84 (84%). In terms of income, 84% earn no more than Rp. 2,000,000. The majority have lived with diabetes for less than ten years (81%) and have the most complications in the form of hypertension (45%). In particular, 86% have never received education on foot care knowledge. However, the high Foot Care Knowledge score (91%) indicates strong knowledge of foot care. Clinical nurses are recommended to integrate routine foot screenings into outpatient care, while optimizing family engagement and leveraging patients' daily rituals as sustainable preventive educational strategies against diabetic foot ulcers.